Curative reconstruction of a cerebral aneurysm by flow diversion with the Pipeline embolisation device in a patient with Loeys-Dietz syndrome. (16th October 2014) - Colby, Geoffrey P; Lin, Li-Mei; Zeiler, Steven R; Coon, Alexander L
Abstract : Loeys-Dietz syndrome is a recently described connective tissue disorder with a natural history of extreme vessel tortuosity and aggressive arterial aneurysm formation and rupture. This is the case of a 23-year-old woman with a large, dysplastic cavernous aneurysm who had successful endovascular treatment by flow diversion with the Pipeline embolisation device. Ten-month follow-up demonstrated complete aneurysm occlusion and curative reconstruction of the parent vessel without evidence of vessel injury or dissection. Endovascular treatment with flow-diverting devices is a valid treatment option and can be performed safely and effectively in this complex patient population.